2012
DOI: 10.1111/jvp.12027
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of maropitant citrate dosed orally to dogs at 2 mg/kg and 8 mg/kg once daily for 14 days consecutive days

Abstract: The pharmacokinetics of maropitant were evaluated in beagle dogs dosed orally with Cerenia® tablets (Pfizer Animal Health) once daily for 14 consecutive days at either 2 mg/kg or 8 mg/kg bodyweight. Noncompartmental pharmacokinetic analysis was performed on the plasma concentration data to measure the AUC(0-24) (after first and last doses), Ct (trough concentration-measured 24 h after each dose), Cmax (after first and last doses), tmax (after first and last doses), λz (terminal disposition rate constant; after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
8
1
Order By: Relevance
“…The C max (maximum plasma concentration) achieved at steady state was similar to what is reported on the label for dogs that received maropitant orally at 2 mg/kg for 14 days, as well as a single intravenous 2 mg/kg dose (Lesman, Boucher, Grover, Cox, & Bridgood, ). The C avg (mean average concentration) at steady state in the current study was slightly lower, but similar to the C max reported after administration of a single dose of maropitant administered orally at 2 mg/kg in healthy horses and dogs (Benchaoui et al, ; Berryhill et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…The C max (maximum plasma concentration) achieved at steady state was similar to what is reported on the label for dogs that received maropitant orally at 2 mg/kg for 14 days, as well as a single intravenous 2 mg/kg dose (Lesman, Boucher, Grover, Cox, & Bridgood, ). The C avg (mean average concentration) at steady state in the current study was slightly lower, but similar to the C max reported after administration of a single dose of maropitant administered orally at 2 mg/kg in healthy horses and dogs (Benchaoui et al, ; Berryhill et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…With its once daily dosing, it also provides a convenience factor that is ideal for both inpatients and outpatients. It is labeled for once daily use up to 5 consecutive days due to concerns for accumulation, but 1 study has shown it can be given up to 14 consecutive days in healthy dogs with few to no side effects . In the current study, 8 dogs received maropitant longer than 5 days with no adverse effects noted.…”
Section: Discussionmentioning
confidence: 76%
“…For example, the variability in maropitant C max (95% confidence interval) was 62–151 ng/mL (approximately a 2.5‐fold range) at 8 mg/kg p.o. after the first dose in a multiple dose study (Lesman et al ., ). Similarly, the variability of the AUC was quite large with a 95% confidence interval of 555–1500 h·ng/mL (approximately 3‐fold range).…”
Section: Discussionmentioning
confidence: 97%